2020
DOI: 10.3390/ani10020192
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Non-Fibrous Carbohydrate (NFC) to Neutral Detergent Fiber (NDF) Ratio Change on Rumen Bacteria in Sheep Based on Three Generations of Full-Length Amplifiers Sequencing

Abstract: The study was conducted to investigate the effects of dietary NFC/NDF ratio change on rumen bacteria in sheep. Twelve Karakul sheep were assigned randomly into four groups fed with four dietary NFC/NDF ratios of 0.54, 0.96, 1.37, and 1.90 and they were assigned into groups 1, 2, 3, and 4, respectively. The experiment was divided into four periods: I (1–18 d), II (19–36 d), III (37–54 d), and IV (55–72 d). In each period, the first 15 d were used for adaption, and then rumen fluid was collected for 3 d from eac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Regardless of diet, the 16S rDNA high-throughput sequencing technology revealed that the microbial community of the lamb was dominated by Bacteroidetes and Firmicutes at the phylum level ( Figure 2 ). Similar findings have been observed in Karakul sheep [ 42 ] and other sheep [ 43 , 44 ]. For the ruminants, Firmicutes play a considerable role in degradation of the fiber and cellulose [ 45 ].…”
Section: Discussionsupporting
confidence: 90%
“…Regardless of diet, the 16S rDNA high-throughput sequencing technology revealed that the microbial community of the lamb was dominated by Bacteroidetes and Firmicutes at the phylum level ( Figure 2 ). Similar findings have been observed in Karakul sheep [ 42 ] and other sheep [ 43 , 44 ]. For the ruminants, Firmicutes play a considerable role in degradation of the fiber and cellulose [ 45 ].…”
Section: Discussionsupporting
confidence: 90%
“…It was reported in human studies that a low abundance of Succinivibrio is correlated with gastrointestinal disorders and loss of intestinal integrity in the colon ( Hespell, 1992 ). Moreover, Succinivibrio has been reported to degrade cellulose and hemicellulose ( Pu et al, 2020 ). Although Pseudomonas belongs to Proteobacteria phylum, its ability to adapt to degrade fiber has been previously reported ( Guo et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, given the ongoing NFC strategies used in the passageways business (Shr _ IVastava and Shr _ IVastava, 2021), it is thought of as very hard to carry out the framework in an inn climate because of cost limitations (Nguyen et al, 2019). These are brought about by the NFC being restricted to detached cards, which require significant expenses to create for every client, particularly in an inn climate, as the number of cards would be an enormous issue to keep up with and, moreover, inclined to be misplaced or obtained from clients, which creates an immense hole in the information enrollment as well as safekeeping trailed by the expenses to produce additional tokens (Pu et al, 2020;Wiastuti et al, 2020). The data set in the NFC framework requires significant complex calculations to oversee, whereas data put away in an outside data set requires exceptional access (Xie et al, 2020).…”
Section: Research Hypothesesmentioning
confidence: 99%